Thrombocytosis in children and adolescents: classification, diagnostic approach, and clinical management - Stockklausner, Clemens; Duffert, Christin; Cario, Holger; Knöfler, Ralf; Streif, Werner; Kulozik, Andreas (Annals of hematology, 2021)
Secondary thrombocytosis is a frequent secondary finding in childhood infection and inflammation. Primary hereditary thrombocytosis may be caused by germline mutations within the genes encoding key regulators of thrombopoiesis, i.e., thrombopoietin (THPO) and its receptor c-MPL (MPL) or the receptor’s effector kinase Januskinase2 (JAK2). Furthermore, somatic mutations in JAK2, MPL, and in the gene-encoding calreticulin (CALR) have been described to act as driver mutations within the so-called Philadelphia-negative myeloproliferative neoplasms (MPNs), namely essential thrombocythemia (ET), polycythemia vera (PV), and primary myelofibrosis (PMF). Increasing knowledge on the molecular mechanisms and on the clinical complications of these diseases is reflected by the WHO diagnostic criteria and European LeukemiaNet (ELN) recommendations on the management of adult MPN. However, data on childhood thrombocytosis are rare, and no consensus guidelines for pediatric thrombocytosis exist. Current literature has highlighted differences in the epidemiology and molecular pathogenesis of childhood thrombocytosis as compared to adults. Furthermore, age-dependent complications and pharmacological specificities suggest that recommendations tailored to the pediatric population are necessary in clinical practice. Here we summarize literature on classification, diagnostics, and clinical management of childhood thrombocytosis.